Eutherian mammals use diverse strategies to initiate X-chromosome inactivation during development - Okamoto, Ikuhiro; Patrat, Catherine; Thépot, Dominique; Peynot, Nathalie; Fauque, Patricia; Daniel, Nathalie; Diabangouaya, Patricia; Wolf, Jean-Philippe; Renard, Jean-Paul; Duranthon, Véronique; Heard, Edith (Nature (London), 2011)
Mice out of step on X inactivation X-chromosome inactivation is an essential process in female mammals that compensates for the presence of two X-chromosomes by suppressing gene expression from one of them. A study of the early developmental time course of X-chromosome inactivation in mice, rabbits and humans shows that the processes in mice, in which most of previous analyses have been done, differ significantly from those in other eutherian species. The study highlights a diversity in X-inactivation regulation that may reflect the changing nature of developmental processes during evolution. X-chromosome inactivation (XCI) in female mammals allows dosage compensation for X-linked gene products between the sexes 1 . The developmental regulation of this process has been extensively investigated in mice, where the X chromosome of paternal origin (Xp) is silenced during early embryogenesis owing to imprinted expression of the regulatory RNA, Xist (X-inactive specific transcript). Paternal XCI is reversed in the inner cell mass of the blastocyst and random XCI subsequently occurs in epiblast cells. Here we show that other eutherian mammals have very different strategies for initiating XCI. In rabbits and humans, the Xist homologue is not subject to imprinting and XCI begins later than in mice. Furthermore, Xist is upregulated on both X chromosomes in a high proportion of rabbit and human embryo cells, even in the inner cell mass. In rabbits, this triggers XCI on both X chromosomes in some cells. In humans, chromosome-wide XCI has not initiated even by the blastocyst stage, despite the upregulation of XIST . The choice of which X chromosome will finally become inactive thus occurs downstream of Xist upregulation in both rabbits and humans, unlike in mice. Our study demonstrates the remarkable diversity in XCI regulation and highlights differences between mammals in their requirement for dosage compensation during early embryogenesis.